Effects of Azospirillum lipoferum strain isolated from Al Jabal Al Akhdar region and wheat straw on some physiological properties and nitrogen content of Triticum aestivum cultivars - Attitalla, Idress H. (Al-Mukhtar Journal of Sciences, 2011)
Azospirillum was abundant in high population levels and recorded 1.1 × 103 – 13.2 × 104 CFU/g in 23 soil samples collected from the rhizosphere of 24 plants grown in different sites distributed in El-Jabal Elakhdr eco-region. According to cell-morphological, cultural and biochemical characteristics, fifteen A. lipoferum isolates were identified. The effect of A. lipoferum (isolate R23) inoculation and / or wheat straw (0.5 and 10 T/h) amendment on the grouth and N2 fixation of two wheat cultivars (Giza 167 and local cultivar) was determined in pot experiments using the difference method (DM). Azospirillum inoculation resulted in accumulation of fixed nitrogen, and N% from atmosphere being 36.7 and 12.9% for wheat Giza 167 and the local wheat cultivar, respectively. Straw amendment reduced %N from atmosphere to 9.7 and 11.2% at 5 and 10 T/h, respectively for wheat local cultivar and recorded 23.9 and 20.1% for wheat cultivar. Giza 167. Rational nitrogen fertilization (180 kg N/h) recorded the lowest %N from air and recorded 7.1 and 11.2% for wheat local and Giza 167 cultivars, respectively. The highest levels of increased growth parameters were obtained by N-fertilization in both inoculated and uninoculated plants for both cultivars. Azospirillum inoculation induced shoot Mg and P content, but not Ca in both cultivars. Organic matter addition had no significant effects in both cultivars used in the present study and such outcome needs further assessment.